Multilateral Peacekeeping Operations in Africa: A Case Study of Liberia - Talibu, Oladimeji (Kashere Journal of Politics and International Relations, 2025)
Africa has become a theatre of conflicts for the most part of post-independent years. Nearly all corners of Africa have experienced one form of conflict or the other. The most protracted of it all was that of Liberia, which broke out in the last decade of the 20th Century. The protracted war clearly put the sub-regional organization in a precarious situation. Such situation led to the formation of ECOMOG IN 1990, with the support from other global multilateral bodies. The current research thus examines the role of ECOWAS peacekeeping missions in conflict management and peace-building in Africa. It seeks to assess the background of ECOWAS intervention in Liberia and establishes the rationale for the establishment of sub-regional mechanism to intervene in the Liberian civil war. The United Nations Article 53 (8) gives substantial power to sub-regional and regional multilateral bodies in mediating in the conflict situation within regions and such authorization provided basis for ECOWAS intervention in Liberia in 1990s. It is within this international legal framework that the articles explores the role that the sub-regional organization played in stemming the tide of war in Liberia. In doing this, the researchers used interview transcripts, media reports, textbooks, articles and government records as sources of data while qualitative content analysis is employed in interpreting the data. In terms of theoretical underlining, regional conflict resolution is used to understand the ECOWAS involvement in Liberian civil war